Analysis of rational food for children with chronic gastropathology - Kramarenko, Natalya; Skriabina, Ekaterina; Sapa, Natalia (ScienceRise: Medical Science, 2019)
Diseases of the digestive system in children occupy a leading place in the structure of the somatic pathology of childhood. Eating disorders, eating substandard food, overeating and inadequate chewing, eating spicy foods, eating a dry meal, as well as monotonous malnutrition the most important causes of acute and chronic diseases of the stomach and intestines. Therefore, the strategy of therapeutic measures in diseases of the digestive system is aimed at correcting metabolic disorders and adequately providing energy and constructive metabolism. The aim of our study was to analyze the actual nutrition of children with chronic pathology of the upper gastrointestinal tract. Materials and methods. 102 patients with chronic pathology of the upper gastrointestinal tract, aged from 3 to 17 years, were surveyed. A questionnaire was created for the survey, which included questions regarding ideas about proper nutrition, diet, the patient's usual menu and his dietary preferences. Patients were divided into 4 age groups. Results. According to our research, patients suffering from diseases of the upper GI tract, in general, try to adhere to the diet. Differences were observed in compliance with the diet, the type of heat treatment of food and the preferred dishes in children in different age groups. Younger children and preschoolers are more likely to follow the doctor’s recommendations on nutrition, while children in primary and high school often violate their diet or use improperly processed foods. The main violations in the diet occur due to the use of "fast food", sweets and bakery products in large quantities. Conclusion. Given that most of the violations in the diet are in the primary and high school age groups, it was concluded that more attention should be paid to patients of this age and to explain to them about the need to comply with the recommendations of doctors on diet. Introduce measures to organize proper nutrition and control for this age group. The results of this study will serve as the basis for the development of motivating programs for patients with gastrointestinal diseases for following them recommendations on nutrition